Types of physical activity and motivation to practice physically activity for primary school and the role of parents in forming the healthy behavior - DawoodAl-Sudani, AliAziz; MatarAL-Bkhati, Dr.Maytham Jabar (International Journal of Psychosocial Rehabilitation, 2020)
According to prof. dr. Barbara Woynarowska MD (2010) physical activity is a physical load (work of the skeletal muscles accompanying with many functional changes in the body, effort, energy expenditure), of a person in everyday life, study, work, play, structured exercise programs. Physical activity is essential to human at every age group and every stage of life. Human’s health is shaped in all phases and stages of his life. Importance of movement, changes and evolves with age of a man, but always remains one of the main factors determining the health. Physical activity is an important determinant of physical fitness and as such can have strong influence on motor fitness (Iwona Kiełbasiewicz– Drozdowska, 2001).